Increasing profitability and water use efficiency of triple rice crop production in the Mekong Delta, Vietnam - NHẪN, P.P.; HÒA, L.V.; QUÍ, C.N.; HUY, N.X.; HỮU, T.P.; MACDONALD, B. C. T.; Tuong, T.P. (Cambridge University Press, 2016)
Rice production in the Mekong Delta, Vietnam is threatened by future water scarcity caused by changing rainfall patterns and increasing irrigation costs. To improve resilience of the triple rice farming system to future climate-related stresses, profitability needs to be increased through water use efficiency, fertilizer management and planting methods.During four cropping seasons in 2011–13, alternate wetting and drying (AWD) irrigation was applied in the triple rice production area within An Giang Province, Vietnam. An issue with the application of AWD is the prevalence of acid sulphate soils in the Mekong Delta. Three types of irrigation management were tested; continuously flooded (CF) where the water in the paddy was maintained at 5 cm; AWD where the water level was allowed to fall to 15 cm below the ground surface, at which point the field was irrigated until the water level was at 1 cm above the ground surface (designated −15 cm); AWD where the water level was allowed to fall to 30 cm below the ground surface before irrigation until the water level was at 1 cm above the ground surface (designated −30 cm). Two further experiments were also undertaken which examined the planting method (transplant v. direct sowing) and phosphorus rate on rice yield. There was no effect on yield caused by P fertilizer rate and irrigation management in any year, and there was no significant effect on soil pH or salinity caused by irrigation management. Overall net profitability was greatest for the AWD treatments because of the reduction in pumping and labour costs in the dry season. Transplanted rice improved yields, but the labour cost reduced overall profitability. The study shows that AWD (−15 cm) can be safely applied in acid sulphate soil areas within the triple rice areas of An Giang Mekong Delta and saved at least 0·27 of total irrigated water quantity used during three of the six cropping seasons. The increased profitability of the AWD rice production system will help to improve the resilience of triple rice cropping systems to future water scarcity.